Pengaruh NU Care-Lazisnu Terhadap Kepercayaan Muzakki di Kabupaten Lampung Tengah - Saryono; Subandi Subandi; A. Muslimin (Bulletin of Community Engagement, 2025)
This research is motivated by the potential role of zakat, infaq, and shodaqoh (ZIS) in supporting poverty alleviation programs in Central Lampung District. When managed properly by amil institutions that have earned the trust of muzakki (donors), ZIS can significantly assist the government in reducing poverty. This study aims to analyze the influence of NU Care-LAZISNU on muzakki trust in Central Lampung by examining three variables: program quality, quality of public relations, and quality of rebranding. The research uses a quantitative approach with data collected through questionnaires distributed via Google Forms, and a Simple Random Sampling technique involving 100 respondents. The analysis includes validity and reliability tests, simple linear regression, hypothesis testing using t-tests and f-tests, and the coefficient of determination (R²) analysis, with data processed using SPSS version 21.00 for Windows. The results show that the Adjusted R² value is 0.521, meaning 52.1% of the variation in muzakki trust can be explained by the variables of program quality, public relations quality, and rebranding quality, while the remaining 47.9% is influenced by other factors outside the model. This study demonstrates that NU Care-LAZISNU’s efforts to improve service quality, transparency, and rebranding significantly enhance muzakki trust, thereby increasing zakat participation and supporting poverty alleviation in Central Lampung.